2019
DOI: 10.1002/mame.201900042
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Lignocellulose Fibers with Higher Thermal Stability through Natural Fiber Welding

Abstract: This study reveals how natural fiber welding (NFW) can be used to engineer biopolymer materials with improved thermal stability. First, it is shown how NFW without binders improves lignocellulose yarn thermal stability by ≈17 °C, primarily by condensing microfibril structure. Next, silanized‐cellulose nanofibrils (Si‐CNFs) are developed as NFW binders; this silanization process alters CNF physical and thermal properties. During pyrolysis, Six Oy networks form, which delay CNF decomposition (up to 37 °C), slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
(71 reference statements)
1
5
0
Order By: Relevance
“…Samples (ca. 50 mg) were dried at 135 °C to remove adventitious H 2 O, heated (10 °C min –1 in air) to 900 °C, then held isothermal at 900 °C for 15 min. Because combustion in air leaves minimal carbonaceous char, final sample mass values (after the isothermal step) revealed the relative amount of TiO 2 within each composite (compared to controls absent TiO 2 NP).…”
Section: Methodssupporting
confidence: 89%
“…Samples (ca. 50 mg) were dried at 135 °C to remove adventitious H 2 O, heated (10 °C min –1 in air) to 900 °C, then held isothermal at 900 °C for 15 min. Because combustion in air leaves minimal carbonaceous char, final sample mass values (after the isothermal step) revealed the relative amount of TiO 2 within each composite (compared to controls absent TiO 2 NP).…”
Section: Methodssupporting
confidence: 89%
“…Thus, natural fiber welding offers a simple and green approach to further enhance and tailor the properties of biopolymer yarns and composites. [151] As previously mentioned, the main issue regarding any application of ILs on commercial scale is solvent recovery and re-use. As known, recovery by evaporating volatiles is energy demanding.…”
Section: Regeneration Of Cellulose From Ilsmentioning
confidence: 99%
“…Thus, natural fiber welding offers a simple and green approach to further enhance and tailor the properties of biopolymer yarns and composites. [ 151 ]…”
Section: Regeneration Of Cellulose In Different Physical Formsmentioning
confidence: 99%
“…[30] Compared with conventional natural biopolymer processing methods that require toxic solvents or full dissolution, NFW is more environmentally friendly since many common ILs are non-toxic and can be recycled. [32] In addition, NFW is extremely versatile; our previous studies have successfully demonstrated fiber-welded wearable supercapacitors, [8] water treatment catalysts, [11,33] thermally stable textile yarns, [34] and most recently polyionic biocomposites. [35] In the present study, antimicrobial linen powder containing various mass loadings of Ag NPs was fabricated.…”
Section: Introductionmentioning
confidence: 99%